Efeitos da variação do teor de umidade da madeira no processo de lixamento - Lima, Larissa Ribas de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The process of sanding wood is little known and industries use it in a practical way without having studied their best conditions before. There are few studies involving this type of machining. On this basis, this paper studied the effects of varying moisture content of the wood surface quality after the sanding process. It was used a sanding machine with flat horizontal cut parallel to the fibers, using: 02 different species (Pinus elliottii and Corymbia citriodora); 01 sanding abrasive (aluminum oxide) and 03 different particle size abrasives ( P80 , P100 and P120 ) . Initially, the pieces were acclimatized ( 2 ± 7% , 12% and 17% ± 2 ± 2 ) and subsequently passed by the sanding process, and therefore, the surface roughness was analyzed. For each condition, were performed 06 repetitions totaling 54 trials for each species. We analyzed the effects of wood moisture by capturing the power sanding, rougheness, acoustic emission and maximum temperature during the sanding process. The variation of moisture content produced changes in the surface quality of the finished parts, and these changes were more marked in Pinus than Corymbia. During the sanding process of the specimens with 7 % and 12 % humidity, there was a lower noise emission, power consumption and heating surface. When checking the roughness of these parts after this process, it was observed that the surface quality of them were superior in the parts sanded containing 17 % moisture

O processo de lixamento de madeiras é pouco conhecido e as indústrias o utilizam de forma prática sem ter estudado suas melhores condições. São raras as pesquisas envolvendo esta forma de usinagem. Com base nisto, o presente trabalho estudou os efeitos da variação do teor de umidade da madeira na qualidade superficial da mesma, após o processo de lixamento. Os ensaios foram realizados em uma lixadeira horizontal plana com corte paralelo às fibras, utilizando: 02 espécies diferentes (Pinus elliottii e Corymbia citriodora); 01 lixa com material abrasivo de óxido de alumínio e 03 diferentes granulometrias de lixas (P80, P100 e P120). Inicialmente, as peças foram climatizadas (7% ±2, 12% ±2 e 17% ±2) e posteriormente, passaram pelo processo de lixamento e verificou-se a rugosidade das mesmas. Para cada condição foram feitas 06 repetições totalizando 54 ensaios para cada espécie. Foram analisados os efeitos da umidade da madeira através da captação da potência de lixamento, rugosidade, emissão acústica e temperatura máxima durante o lixamento. A variação do teor de umidade produziu mudanças na qualidade superficial das peças acabadas sendo estas mudanças mais acentuadas no Pinus do que no Corymbia. Durante o processo lixamento dos corpos de prova com 7% e 12% de umidade, houve uma menor emissão acústica, potência consumida e aquecimento da superfície. Ao verificar a rugosidade destas peças após este processo, se observou que a qualidade superficial delas foram superiores as peças lixadas que continham 17 % de umidade
Keywords: Trabalhos em madeira; Madeira - Efeito da umidade; Usinagem; Aspereza de superfície; Lixadeiras; Pinus elliottii; Eucalipto; Woodwork